Changes of growth-climate relationships of Smith fir forests along an altitudinal gradient - Zheng, Jiacheng; Yang, Jing; Jia, Hengfeng; Lyu, Lixin; Langzhen, Jiayang; Zhang, Qi-Bin (Journal of forestry research, 2024)
Temporal changes in the relationship between tree growth and climate have been observed in numerous forests across the world. The patterns and the possible regulators (e.g., forest community structure) of such changes are, however, not well understood. A vegetation survey and analyses of growth-climate relationships for Abies georgei var. Smithii (Smith fir) forests were carried along an altitudinal gradient from 3600 to 4200 m on Meili Snow Mountain, southeastern Tibetan Plateau. The results showed that the associations between growth and temperature have declined since the 1970s over the whole transect, while response to standardized precipitation-evapotranspiration indices (SPEI) strengthened in the mid- and lower-transect. Comparison between growth and vegetation data showed that tree growth was more sensitive to drought in stands with higher species richness and greater shrub cover. Drought stress on growth may be increased by heavy competition from shrub and herb layers. These results show the non-stationary nature of tree growth-climate associations and the linkage to forest community structures. Vegetation components should be considered in future modeling and forecasting of forest dynamics in relation to climate changes.